KRITIK SOSIAL DALAM NOVEL TERE LIYE: SI PUTIH - Irawan, Putri Calista; Balqis, Syira Amanah; Riadi, Bambang; Prayogi, Rahmat (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to describe the forms of social criticism found in the novel Si Putih by Tere Liye by examining their relation to the author’s background, the social realities of society, and readers’ responses. This research is grounded in the theory of literary sociology, which emphasizes that literary works reflect social realities creatively expressed through the author’s experiences and imagination. The study employs a descriptive qualitative method with a sociological approach to literature. Data were collected through an intensive reading of the novel, analysis of the author’s social background, and interpretation of the social meanings embedded in the narrative. The findings reveal that Si Putih contains various forms of social criticism, including critiques of social inequality, humanity, and moral disparity in society. These criticisms are conveyed through the depiction of character conflicts, settings, and dialogues that hold reflective meaning. The novelty of this research lies in its comprehensive analysis that connects the intrinsic elements of the novel with the author’s social dimension and readers’ perspectives, thereby reinforcing the understanding that literature is not merely an aesthetic product but also a medium of social communication that fosters awareness and critical sensitivity toward societal realities.